2012
DOI: 10.1111/j.1601-5215.2011.00636.x
|View full text |Cite
|
Sign up to set email alerts
|

Obstetric complications and neurological soft signs in male patients with schizophrenia

Abstract: complications and neurological soft signs in male patients with schizophrenia.Objective: The study investigated the relationship between neurological soft signs (NSS) and obstetric complications (OCs) in patients with schizophrenia. Methods: Sixty-three male patients with schizophrenia were divided into two subgroups, based on the OCs presence or absence, which were compared in relation to NSS prevalence. After that, a Person's correlation test was performed to explore the correlation between NSS and OCs sever… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…Obsessive-compulsive disorder and schizophrenia are, in fact, considered to be neurodevelopmental disorders with dysfunctional frontal subcortical circuitry 37. A possible common neurodevelopmental origin is suggested by several lines of evidence: both obsessive-compulsive disorder and schizophrenia have a juvenile onset and chronic course; relevant neurological soft signs are present in both diseases;38,39 patients with obsessive-compulsive disorder and those with schizophrenia have more adverse perinatal experiences than healthy controls;38,40 obsessive-compulsive symptoms are clinically important phenomena in people with schizophrenia; and people with obsessive-compulsive disorder often experience psychosis 41. In line with this theory, the impaired capacity to experience and express emotions may be seen as another chronic consequence of the same neurodevelopmental origin of the two diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Obsessive-compulsive disorder and schizophrenia are, in fact, considered to be neurodevelopmental disorders with dysfunctional frontal subcortical circuitry 37. A possible common neurodevelopmental origin is suggested by several lines of evidence: both obsessive-compulsive disorder and schizophrenia have a juvenile onset and chronic course; relevant neurological soft signs are present in both diseases;38,39 patients with obsessive-compulsive disorder and those with schizophrenia have more adverse perinatal experiences than healthy controls;38,40 obsessive-compulsive symptoms are clinically important phenomena in people with schizophrenia; and people with obsessive-compulsive disorder often experience psychosis 41. In line with this theory, the impaired capacity to experience and express emotions may be seen as another chronic consequence of the same neurodevelopmental origin of the two diseases.…”
Section: Discussionmentioning
confidence: 99%
“…As an indication of that, delayed speech or walking in childhood are important risk factors not only for neurological soft signs (Peralta et al, 2011), but also for schizophrenic psychoses (Welham et al, 2009). Moreover, some studies found a relationship between a history of obstetric complications and neurological soft signs (Bersani et al, 2012;Peralta et al, 2006) in schizophrenia patients. However, this relationship remains controversial as some found a negative relationship in schizophrenia (Mrad et al, 2010) or first-episode psychosis (Boks et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…The neurological soft signs (NSS) are minor neurological abnormalities in sensory and motor performances well established in schizophrenia. 11 , 12 They have been described in patients with BD 13 , 14 not only during the mood dysregulation episodes, but also in the euthymic phase of the disease. 15 In addition, various research has observed deficits in NSS expression and deficits in executive functions, suggesting that the disturbances in the two areas of brain functioning domains may result from the alteration of similar underlying neurobiological substrates.…”
Section: Introductionmentioning
confidence: 99%